Rebranding in the NFL - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2020)
After years of criticism, the NFL's Washington team announced in July 2020 that they would be retiring their racist name. This case covers the decision to engage in rebranding of the team, occurring against the backdrop of massive protests against racial injustice across the United States. Students are asked to discuss why the team is changing their name now, what the team should do in order to move forward in a respectful way, and to ponder the issues related to rebranding, especially as they pertain to offensive brand names.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business and Management